Factors Affecting the Impact of Child Advocacy Offices in Canada - Howe, R. Brian (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2009)
International interest in children’s rights and in official child dvocacy agencies responsible for pomoting the rights and voices of children is increasing. This article examines the conventional wisdom on factors that enhance the impact of these agencies. It does so through a stucly on the impact of provincial child dvocacy offices in Canada. In line with conventional wisdom, the findings show that, in general, a higher level of impact is associated with offices that are independent from government, exclusively focused on children, accessible to children, and that have a wide marulute, strong statutory powers, and a broad advocacy function. But what also is suggested in the findings is the importance of a factor not given attention in the conventional wisdom - slcillful ledership in the context of a receptive political culture. In conjzinction with or in the absence of othe facilitating factors, leadership in a supportive political environment can play a significant role in acluancing the rights of children. On assiste dans le monde entier h un regain d’inte’rzt pour les h i t s des enfants et les organismes de &fense de l’enfance qui sont responsables de la promotion des droits et de la voix des enfants. Duns cet article, on examine les ide’es resues sur les facteurs qui rehaussent l’influence de ces organismes et, notamment, par une e’tucle sur l’influence des organismes provinciaux de de’fense de l’enfance au C a d . A l’instar des ide’es repes, l’e’tude conclut qu’un niveau plus ileue’ d’injluence est observe’ dans les organismes qui sont indipendants des pouvoirs publics, exclusivement axes sur les enfants, accessibles aux enfants, et cew qui ont un waste mandat, lles robustes pouwoirs statutuires et une ample fonction de repr6sentation. Cependant, les re’sultuts montrent aussi l’importunce d’un facteur qui n’a pas suscite’ lJmt6rZt des wues traditionnelles : le leadership awist! dans le contexte d’une culture politique re’ceptiwe. Une lles conclusions tire’es weut qw conjointernent awec, ou en l’absence, d’autres fucteurs facilitateurs, le ledership peut jouer un r8le iml ortandt ans la promotion des droits lles enfants.